CLINIC-MORPHOLOGICAL ANALYSIS OF THE APPLICATION OF THE MONONUCLEAR FRACTION OF AUTOLOGOUS BONE MARROW CELLS IN ENDOMYOCARDIAL IMPLANTATION IN A PATIENT WITH SEVERE ISCHEMIC MYOCARDIAL DYSFUNCTION OF THE LEFT VENTRICLE - Ye. N. Kliever; A. M. Cherniavsky; Ye. A. Pokushalov; Ye. E. Kliever; А. М. Volkov (Вестник трансплантологии и искусственных органов)
Aim. The purpose of this study is to conduct clinic-morphological analysis following intramyocardial administration of a mononuclear fraction of bone marrow stem cells in a CHF patient suffering from ischemic heart disease. In October 2007 the patient underwent surgery, with a mononuclear fraction of bone marrow stem cells implanted with the use of a NOGA system. The patient was then put on a waiting list for heart transplantation. After 2-year follow-up amelioration was observed, LVEF increased from 22 to 27%, LF end systolic volume dropped from 265 ml to 250 ml. All these positive developments indicated the stabilization of hemodynamic indicators and enabled to wait for orthotopic heart transplantation which was performed in December 2009.